The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.5028/jatm.2010.02010915
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the e-beam profile of a single carbon nanotube field emission device for electric propulsion systems

Abstract: Preliminary studies on field emission (FE) arrays comprised of carbon nanotubes (CNT) as an electron source for electric propulsion system show remarkably promising results. Design parameters for a carbon nanotube (CNT) field-emission device operating on triode configuration were numerically simulated and optimized in order to enhance the e-beam focusing quality. An additional focus gate (FG) was integrated to the device to control the profile of the emitted e-beam. An axisymmetric finite element model was dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Figure 8 shows that the beam divergence decreases by increasing the gate voltage. Mologni et al have reported the dependence of the divergence of an individual CNT field emitter [33]: the beam divergence increases by increasing the anode-cathode distance.…”
Section: Modelingmentioning
confidence: 99%
“…Figure 8 shows that the beam divergence decreases by increasing the gate voltage. Mologni et al have reported the dependence of the divergence of an individual CNT field emitter [33]: the beam divergence increases by increasing the anode-cathode distance.…”
Section: Modelingmentioning
confidence: 99%